2002
DOI: 10.1046/j.1523-1747.2002.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Related to Oxygen Free Radicals in Human Skin: A Study Comparing Healthy Epidermis and Skin Cancer Tissue

Abstract: In vitro studies with tumor cells have demonstrated that oxygen free radicals are involved in the development of skin cancers and that variations in the body's defense mechanisms can modify the course of the disease. To assess the validity of this hypothesis in spontaneous tumors, we determined glutathione S-transferase, superoxide dismutase, reduced and oxidized glutathione, and thiobarbituric acid reactive substances in healthy whole skin (n = 95), dermis (n = 73), and epidermis (n = 69). The values were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
3
27
0
2
Order By: Relevance
“…GSSG is toxic and in normal circumstances GSSG/GSH ratio in the cells is kept very low, i.e. < 0.01 in erythrocytes [24], and close to 1:10 in the skin [25][26][27]. Increased glutathione redox ratio refers to insufficient redox-control over prooxidative mecha nisms.…”
Section: Discussionmentioning
confidence: 99%
“…GSSG is toxic and in normal circumstances GSSG/GSH ratio in the cells is kept very low, i.e. < 0.01 in erythrocytes [24], and close to 1:10 in the skin [25][26][27]. Increased glutathione redox ratio refers to insufficient redox-control over prooxidative mecha nisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a persistent oxidative microenvironment in cancer tissue including BCC (5,14). Higher levels of reactive biomolecules derived from ROS mediated lipid peroxidation such as TBARS, or DNA derived 8-hydroxi -2-deoxyguanosine (80HdG), were found in BCC lesion compared to healthy controls (6).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma proteins serve a similar albeit non-specific detoxification capacity. The skin defense system includes the enzymes GST, GPx, SOD, and GRx, CAT, which are higher in the epidermis, and thiobarbituric reactive substances which are prevalent in the dermis [77][78] and NAT1. An imbalance between bioactivation and detoxification processes results in an excess of reactive intermediates that can contribute to the development of drug hypersensitivity syndrome [79][80].…”
Section: Cellular Detoxification Defense Sys-temmentioning
confidence: 99%